Wandalowie w Hiszpanii i Rzymie, czyli Macieja z Miechowa (1457–1523) metoda badania dziejów - Zawadzki, Robert K. (Collectanea Philologica, 2024)
In the article Robert K. Zawadzki examines the representation of the Vandals in the historical work entitled Chronica Polonorum of Maciej of Miechów. This race who settled on the south coast of the Baltic Sea provided fertile ground for the Polish writer to articulate his ideas about the origins of the Polish nation. By examining these historical tales, the author shows how the author constructed an image of journeys of the great nation in keeping with the patriotic and moralistic goals and context of his own work, while individually creating a vision of Poles as Vandals who occupied Transdanubian Pannonia, attacked the Roman provinces, devastated wide areas of Gaul, crossed into Spain, moved into North Africa and captured Rome. This combination of such historical narrative material aims to highlight both the splendor of ancient Polish history and the fundamental unity of the Polish and European history.